Pendampingan Santri dalam Menghafal Al-Quran dengan Metode Puzzle di LKSA Ar-Ridlo Peterongan Kabupaten Jombang - Maidatus Sa’diyah; Ahsinatul Kumala; Wawan Herry Setyawan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
An important issue that requires significant attention is the students at the LKSA ar-Ridlo Orphanage's need for motivation to memorize the Qur'an. After learning the fundamentals of Al-Qur'anic reading, pupils at the LKSA ar-Ridlo Orphanage are taught how to memorize verses using the Puzzle method. Three approaches were frequently used to apply learning methods to infants and adults: practical methods, program implementation, and evaluation. Thirty kids from the LKSA ar-Ridlo Santri orphanage participated in this inaugural effort. This service program was attended by 30 students from the LKSA ar-Ridlo Orphanage Santri Boys and Girls. The mentoring program will involve Islamic religious education lecturers at UNHASY Jombang. This service lasts for 3 (three) months, starting from the target of April to August 2023. The result and benefits of this activity include (i) an improvement in the lecturer's memorization abilities of the Al-Qur'an, as evidenced by (a) participants' ability to memorize the Qur'an using the precise makharijul letters and tajwid, and (b) trainees' ability to memorize and teach the Qur'an using the Puzzle method.